Потужність приводу відцентрового нагнітача природного газу - Олійник, Юрій Анатолійович; Саприкін, Сергій Олексійович; Науменко, Світлана Петрівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Отримано формули для потужності приводу відцентрового нагнітача (ВЦН) природного газу, де враховується не тільки механічний та політропний коефіцієнт корисної дії (ККД) ВЦН, але й газодинамічний ККД ВЦН, де враховуються газодинамічні втрати тиску газу та потужності ВЦН. Також в формулі розрахунку потужності приводу ВЦН, що експлуатується, враховується наявність парів конденсату та води в природному газі.

Formulas for drive power of centrifugal supercharger of natural gas are obtained, where efficiency factor (EF) of centrifugal supercharger is equal to product of three EF of centrifugal supercharger: mechanical, polytropic, gas-dynamic. The gas dynamic EF of the centrifugal supercharger is usually not taken into account and is taken equal to one. Gas dynamic EF takes into account the pressure loss of the centrifugal supercharger pumped in the stages and the energy loss due to friction of the centrifugal supercharger impellers in the gas medium. Also in the formula of calculation of drive power of the operated centrifugal supercharger the presence of condensate and water vapors in the natural gas is taken into account, which affects the accuracy of measuring the flow rate of pumped gas in the diaphragm flowmeter. Pumping of pure natural gas is impossible in reality and there are always impurities in natural gas, which must be taken into account to estimate the mass flow rate of gas. For formulas of practical (operated) and theoretical calculations of the drive power of the centrifugal natural gas blower received constant (equal to 0.004) for daily standard gas flow, which simplifies the calculation. The paper presents both precise and simplified formulas for the drive power of a centrifugal natural gas blower.
Determination of fuel gas flow rate in gas pumping unit and compressor station
Keywords: розхід газу; газоперекачувальний агрегат; gas flow rate; gas transfer unit